2013
DOI: 10.1121/1.4794932
|View full text |Cite
|
Sign up to set email alerts
|

Inner speech captures the perception of external speech

Abstract: Talking silently to ourselves occupies much of our mental lives, yet the mechanisms underlying this experience remain unclear. The following experiments provide behavioral evidence that the auditory content of inner speech is provided by corollary discharge. Corollary discharge is the motor system's prediction of the sensory consequences of its actions. This prediction can bias perception of other sensations, pushing percepts to match with prediction. The two experiments below show this bias induced by inner s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 15 publications
4
45
0
2
Order By: Relevance
“…Further electrophysiological evidence for phonological prediction effects has been found for word forms with respect to a speaker's accent (Brunelliere & Soto-Faraco, 2013) as well as during self-initiated speech (Knolle, Schröger, & Kotz, 2013). Predictive mechanisms have been found related to inner speech production (Scott, Yeung, Gick, & Werker, 2013) and may modulate brain responses even down to the level of auditory cortex (Skipper, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Further electrophysiological evidence for phonological prediction effects has been found for word forms with respect to a speaker's accent (Brunelliere & Soto-Faraco, 2013) as well as during self-initiated speech (Knolle, Schröger, & Kotz, 2013). Predictive mechanisms have been found related to inner speech production (Scott, Yeung, Gick, & Werker, 2013) and may modulate brain responses even down to the level of auditory cortex (Skipper, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Just as visual influences on auditory speech processing have long been reported (e.g., Sumby and Pollack, 1954; see Navarra et al, 2012 for review), recent reports have also shown similar effects from articulatory information. For example, subjects’ own silent articulations (Sams et al, 2005; Sato et al, 2013; Scott et al, 2013) influence auditory perception in similar ways as seeing visual speech (although see Mochida et al, 2013). Moreover, receiving haptic or tactile input related to another person’s articulatory movements can also influence auditory speech processing (Fowler and Dekle, 1991; Gick et al, 2008; Gick and Derrick, 2009; Ito et al, 2009; Treille et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This process results in the first-person conscious experience of the episode of inner speech. The proposal that the predicted state may form the basis of the sensory content of inner speech is supported by recent behavioral studies (Scott, 2013; Scott et al, 2013). …”
Section: A New Comparator Account Of Misattributed Inner Speechmentioning
confidence: 90%